An influence of outdoor temperature on thermal performance of windows with a low-emissivity glazing - Burlingis, Arünas; Samajauskienė, Birutė; Ramanauskas, Juozas (Journal of Civil Engineering and Management, 2003)
Heat economy is a pressing issue in all countries with severe climate. The most frequent method to solve the problem is to decrease heat losses in buildings by increasing the thermal resistance of enclosures. The most popular measure to improve windows is the use of low-emissivity coatings and inert gases. The U-value of such glazing unit is mostly dependent on the possibility of coating to reflect IR (infrared) radiation. These coatings are very effective when surface temperatures are high. During service of windows with a change of outdoor conditions (mostly temperature and wind), an U-value of it will suffer changes. The aim of this article is to show an influence of outdoor temperature on thermal performance of windows with a low-emissivity glazing and to determine the differences of declared and design U-values of modern effective windows substantial enough to introduce a concept of a normative design U-value for windows in Lithuania. We have found that differences between declared and design values (under the conditions of Lithuania) reach on average up to 17% for double glazed IG units with one low-E coating. Thus in case of very effective windows, it makes sense to introduce a concept of design U-value for windows in our country.First Published Online: 26 Jul 2012